Thai rice instant granules containing turmeric extract and Phyllanthus emblica fruit pulp: Chronic toxicity and antioxidant profiles in rats and in silico investigation of bioactive compounds - Punvittayagul, Charatda; Thongtharb, Atigan; Umsumarng, Sonthaya; Chaichit, Siripat; Okonogi, Siriporn; Ampasavate, Chadarat; Hongwiset, Darunee; Taya, Sirinya (Frontiers in Toxicology, 2025)
Turmeric (Curcuma longa) and Indian gooseberry (Phyllanthus emblica) are widely used for their ethnopharmacological properties, particularly in ASEAN countries. Recently, our group has formulated Thai rice instant granules containing turmeric extract and P. emblica fruit pulp (TR instant granules); however, their toxicity profile has not been evaluated. This study investigated the long-term safety of TR instant granules in rats and assessed their effect on hepatic antioxidant status. Oral administration at doses of 200, 600, and 2,000 mg/kg body weight for 180 days resulted in no toxic effects, behavioral changes, mortality, or alterations in organ weights or hematological parameters. Significant changes were observed in biochemical markers, but there were no histopathological abnormalities. TR instant granules significantly upregulated hepatic antioxidant genes (Nrf2, GPx, CAT, GR, SOD, and HO-1). Phytochemical analysis identified chlorogenic acid and curcumin as major constituents. In silico molecular docking demonstrated that these compounds strongly bind multiple antioxidant enzymes and the Nrf2–Keap1 complex, supporting their potential as effective modulators of cellular antioxidant defenses. Overall, long-term administration of TR instant granules is safe and may enhance antioxidant mechanisms in rats. These findings support the potential development of TR instant granules as a safe functional food or nutraceutical with antioxidant benefits.